IMPLEMENTASI MODEL PROBLEM BASED LEARNING DAN MAKE A MATCH DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Nabila, Alya; Nashir, M. Ajmul; Febrianti, Nadia; Ferdiyansyah, Aldy; Riandy Agusta, Akhmad; Ayu Pratiwi, Diani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lack of student activeness in learning IPAS in class V SDN Kuin Utara 1 encourages innovation in the teaching and learning process. This study aims to increase student involvement and participation through the application of the POMA model, which is a combination of Problem Based Learning and Make a Match. The method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed an increase in student activeness, ability to work together, and understanding of the material. Students became more enthusiastic and actively involved, although there were still obstacles in time management. The POMA model has proven effective and is recommended as an alternative approach that is aligned with the principles of the Merdeka Curriculum.